2020
DOI: 10.1155/2020/5630296
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and Maternal Complications of Placenta Praevia and Its Risk Factors in Tikur Anbessa Specialized and Gandhi Memorial Hospitals: Unmatched Case-Control Study

Abstract: Background. Placenta praevia is a disorder that happens during pregnancy when the placenta is abnormally placed in the lower uterine segment, which at times covers the cervix. The incidence of placenta praevia is 3-5 per 1000 pregnancies worldwide and is still rising because of increasing caesarean section rates. Objective. To assess and identify the risk factors and maternal and neonatal complications associated with placenta praevia. Method and Materials. Target populations for this study were all women diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 19 publications
(29 reference statements)
7
32
0
6
Order By: Relevance
“…The highest maternal complication in this study was hemorrhage, which required blood transfusion (40.38%) as in Adere study. [ 15 ] In our study, (21.15%) of patients had hysterectomy to control bleeding, interestingly this is similar to what has concluded in previous studies. [ 16 ]…”
Section: Discussionsupporting
confidence: 92%
“…The highest maternal complication in this study was hemorrhage, which required blood transfusion (40.38%) as in Adere study. [ 15 ] In our study, (21.15%) of patients had hysterectomy to control bleeding, interestingly this is similar to what has concluded in previous studies. [ 16 ]…”
Section: Discussionsupporting
confidence: 92%
“…In current study, the mean age of the study population was 31.69±4.04 years (20-35) with 41.0% ≤ 30 years and 59.0% were more than 30 years. This finding was similar to Adere et al [13] advanced maternal age ≥ 35 connoted 6-fold increase in risk of placenta previa, Sorakayalapeta MR et al, [13] major number of cases fell into the age group 25-29years with mean age being 25.6 years Prasanth et al [14] found that the incidence of Placenta previa was highest in the age group of 20-29 years i.e., 72.9%, followed by 30-35 year age group, above 35 year age group and less than 19 year age group, i.e., 20.3%, 5.1%, 1.7% respectively. This is thought to be due to atherosclerotic changes in the uterus resulting in under perfusion and infraction of the placenta, thereby increasing the size of the placenta.…”
Section: Agesupporting
confidence: 93%
“…PPH was most common post-partum complication. This finding is supported by the work of Adere et al 19 Regarding neonatal outcome most of the neonate were normal without complications, 6% neonate were preterm, 2 neonate have IUD, Meconium aspiration syndrome was present in 2 patients and 1 neonate was still born. This finding is supported by the work of Crane et al 20…”
Section: Discussionsupporting
confidence: 75%